Student Acceptance Study of PhET Simulation with an Expanded Technology Acceptance Model Approach - Silviana Nur Faizah; Lia Nur Atiqoh Bela Dina; Ari Kartiko; Muhammad Anas Ma`arif; Moch. Sya'roni Hasan (Journal of Applied Engineering and Technological Science (JAETS), 2023)
Phet simulation is a computer-based practicum simulation medium that helps to increase students’ engagement and understanding through concept visualization. Even though there have been numerous studies on the Technology Acceptance Model (TAM) related to Phet simulation, the TAM study of Phet simulation combined with certain learning methods is rarely observed. We propose an advanced version of TAM by including the external variables of system quality, user characteristics, and instructor. This study is a quantitative design with a descriptive, explanatory type. This model was tested using an online questionnaire disseminated to 49 students that finished taking basic natural sciences subjects using Phet simulation based on problem-based learning. The result showed that system quality has an effect on perceived usefulness, perceived ease of use has an effect on behavioral intention of use, behavioral intention of use has an effect on actual usage, and there is no relationship between instructor quality on perceived usefulness. Grit on perceived ease of use, learner anxiety, and perceived usefulness on the behavioral intention of use. These findings have implications regarding user acceptance of Phet simulation combined with certain learning methods, specifically problem-based learning.